Wasiat Wajibah and Islamic Inheritance Philanthropy: A Socio-Legal Study In Indonesia - Nur Syakirah Binti Mohd Adnan; Rosdiana Rosdiana; ⁠⁠⁠Amin Songgirin; Jejen Jaenudin; Al Fiqri Ardiansyah (Universitas Muhammadiyah Bandung, 2026)
This study examines the role of wasiat wajibah as an adaptive mechanism within Islamic inheritance law in addressing the tension between the rigid structure of farā’iḍ and the evolving realities of Muslim family relations. Existing studies largely focus on doctrinal aspects of inheritance law, but overlook how wasiat wajibah operates empirically as a redistributive and philanthropic instrument within contemporary family contexts. Using a qualitative socio-legal approach with a case study design, this research analyzes 27 inheritance cases from Religious Courts in Indonesia, complemented by in-depth interviews with relevant stakeholders. The findings show that a significant number of cases involve non-genealogical individuals such as adopted children and caregivers who are excluded under classical farā’iḍ despite their substantial social contributions. In response, wasiat wajibah is widely applied as a corrective mechanism, redistributing a portion of the estate to these individuals. While resistance from genealogical heirs remains evident, the majority of cases demonstrate positive social outcomes, including improved welfare and strengthened family cohesion. These results indicate that wasiat wajibah functions not only as a legal instrument but also as a form of intra-family philanthropy grounded in principles of equity and compassion. By integrating maqāṣid al-sharī‘ah, distributive justice, and living law perspectives, this study introduces the concept of affirmative Islamic inheritance philanthropy, demonstrating that Islamic inheritance law can adapt to contemporary social complexities while maintaining normative legitimacy.